Report on the international library and information scientific conference: the past years of BOBCATSSS - Szabó, Dóra; Dani, Erzsébet; Nemes, László (Folia Toruniensia, 2024)
The BOBCATSSS organization, an annual event coordinated by library and information science students from various European universities, fosters collaboration and knowledge exchange within the library and information science (LIS). Since its inception in 1993, BOBCATSSS conferences have served as a significant platform for students, professionals, and academics to present research, discuss contemporary issues, and explore emerging trends in LIS. The unique student-driven nature of the conference ensures the inclusion of fresh perspectives and innovative approaches, reflecting the dynamic and evolving landscape of the discipline. Each year, the conference is hosted by different universities across Europe, promoting cultural exchange and enhancing the international dimension of LIS education and research. The themes of BOBCATSSS conferences are diverse, covering a wide range of topics such as digital libraries, information literacy, knowledge management, and the impact of emerging technologies on information services. By providing an interdisciplinary forum, BOBCATSSS facilitates the development of new ideas and the establishment of professional networks, contributing significantly to the advancement of LIS.